Respuesta :

1rstar
◆ COMPLEX NUMBERS ◆

[tex] given \: expression \: is \: - \\ \\ - 3 {i}^{4} + 2 {i}^{3} + 2 {i}^{2} + \sqrt{ - 9} \\ \\ we \: know \: that \: , \: \\ i = \sqrt{ - 1} \\ \\ {i}^{2} = - 1 \\ \\ {i}^{3 } = - i \\ \\ {i}^{4} = 1 \\ \\ \\ - 3 {i}^{4} + 2 {i}^{3} + 2 {i}^{2} + \sqrt{9} i \\ = - 3 {i}^{4} + 2 {i}^{3} + 2 {i}^{2} + 3i \\ \\ using \: the \: above \: properties \: of \: iota \: (i) \\ \\ = - 3(1) + 2( - i) + 2( - 1) + 3i \\ \\ = - 3 - 2i - 2 + 3i \\ \\ = (- 5 + i) \: \: \: ans.[/tex]
ACCESS MORE